Association of MICA Alleles and Human Leukocyte Antigen B in Turkish Patients Diagnosed With Behçet's Disease - Nilnur EYERCİ; Eda BALKAN; Necmettin AKDENİZ; Sadullah KELEŞ (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate whether or not MHC class I polypeptide-related sequence A (MICA) polymorphisms are associated with the susceptibility to Behçet’s disease (BD) in a Turkish population. Patients and methods: The study included 38 Turkish BD patients (20 males, 18 females; mean age 34±10.9 years) and 51 ethnically matched healthy controls (30 males, 21 females; mean age 36±12.8 years). MICA and human leukocyte antigen B (HLA-B) alleles were determined in all subjects by using the Luminex technology. LABType sequence-specific oligonucleotide MICA test (One Lambda) and sequence-specific oligonucleotide B locus tests (Gene-Probe) were used for the typing studies. Results: A total of 16 MICA alleles were found in BD patients as well as in control subjects. The gene frequency of MICA*006 was significantly higher in the BD patients compared to controls (14.5% vs. 0.9%; odds ratio [OR]: 17.092 95% confidence interval [CI] [2.155~135.554]; p<0.05). When haplotypes were evaluated, an association was found between the haplotypes HLA-B*51-MICA*006 (11.8% and 0.9%; OR: 13.567 95% CI [1.679~109.577]; p<0.001) and HLA-B*51-MICA*009 (27.6% and 13.7%; OR: 2.4 95% CI [1.127~5.109]; p<0.05). Frequencies of HLA-B*49-MICA*004 (0% and 6.8%) and HLA-B*52- MICA*009 (0% and 10.7%) were significantly higher in controls compared to BD patients (p<0.05). Conclusion: Our study shows that the MICA*006 (MICA-A6) and the MICA*009 alleles are associated with BD susceptibility in HLA-B*51 positive Turkish population, particularly in HLA-B*51 patients with MICA*006, which might be considered as a diagnostic biomarker for BD in the future.